The Association between Modifiable Risk Factor with Inflammatory Marker in Knee Osteoarthritis Women - Arnadi, Arnadi; Afriwardi, Afriwardi; Ali, Hirowati; Sahputra, Roni Eka (Open Access Macedonian Journal of Medical Sciences, 2022)
Background: IL-1β and TNF-α are vital inflammatory cytokines in the pathophysiological process of Osteoarthritis (OA). Several risk factors can increase the expression of these cytokines, such as BMI, physical activity, and menopausal status. Aims: This study aims to determine the relationship of modifiable factors with synovial fluid IL-1β and TNF-α levels in knee OA women. Methods: The cross-sectional study was conducted at the orthopedic poly hospital Arifin Achmad Riau Province and Ibnu Sina Hospital in Pekanbaru City. A total of 93 women with knee OA were taken as samples by consecutive sampling. Data were obtained directly from respondents by conducting interviews using a questionnaire, measuring weight and height, examining levels of IL-1β and TNF-α from the synovial fluid using the enzyme-linked immunosorbent assay (ELISA) method. The data were processed computerized using the Person correlation test, One Way Anova, and t-Test. The statistical analysis results were considered significant if the p-value was 0<05. Results: the average age of subjects was 60.67 + 9.99 years, 87.8% aged > 40 years, 84.9% had menopause, and at most had moderate physical activity degrees (51.6%). The mean BMI was 27.18+4.17, the average of IL-1β 424.73+188.01 pg/mL, and TNF-α 105,17+48.98 ng/L. There was a significant positive correlation with moderate strength between BMI and levels of IL-1β and TNF-α synovial fluid (p=0.037, r=0.217, and p=0.047, r=0.207). Conclusion: BMI is a risk factor for IL-1β and TNF-α levels in synovial fluid of knee joints in women with OA, but physical activity and menopausal status are not risk factors.